Vitamins D and E as radiotherapy adjuncts - literature review of preclinical and clinical evidence - Wiśniowska, Ada; Wiśniowski, Maksymilian; Buczek, Kacper; Kozłowska, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction: Radiotherapy (RT) is the fundamental method in cancer treatment, yet tumor resistance and normal tissue toxicity limit its efficacy. Vitamins D and E may modulate RT outcomes through radiosensitization, antioxidant effects, and immune regulation. Methods and Materials: We reviewed preclinical and clinical studies from PubMed, ScienceDirect, ResearchGate, and Google Scholar using keywords like “radiotherapy”, ”radiation”, “vitamin D”, “vitamin E” and “radiosensitivity”. Results: Vitamin D enhances RT response via VDR-mediated DNA damage and reduces toxicity (e.g., mucositis), though hypercalcemia risk requires monitoring. Vitamin E (especially tocotrienols) alleviates mucositis and fibrosis, but excessive doses may compromise RT efficacy by neutralizing tumor-killing ROS. Conclusions: Vitamins D and E show therapeutic potential in RT but require precise dosing and timing to avoid interference with treatment. Personalized strategies and robust clinical trials are needed to establish evidence-based guidelines for their adjuvant use.